Model Matematika (Linier) Populasi Anjing Rabies dengan Vaksinasi - Ahmad Fitri; Tjokorda Bagus Oka; I Nyoman Widana (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2014)
Rabies is an infectious virus that can attack all mammals especially dogs. In Bali, rabies was found in late 2008. One of the solutions done by government for the problem is by giving vaccine to healtly dogs, so that they are not easily infected by the virus. Thus, a mathematical model is needed to analyze the development of dog population in Bali and to determine the limination of dogs birth population and the percentage limination of vaccination that can be possibly done so that the population of dogs infected by rabies becomes extinct. By using analysis of fixed point and stability on the model, the limination of dogs birth population and the percentage limitation of the vaccination was obtained. Lastly, a numeric simulation by using Taylor’s series order was conducted to illustrate and to strengthen the result of the analysis.